Decentralized Supply Chains Subject to Information Delays - Chen, Fangruo (Management Science, 1999)
We consider a supply chain whose members are divisions of the same firm. The divisions are managed by different individuals with only local inventory information. Both the material and information flows in the supply chain are subject to delays. Under the assumption that the division managers share a common goal to optimize the overall performance of the supply chain (i.e., they act as a team), we characterize the optimal decision rules for the divisions. The team solution reveals the role of information leadtimes in determining the optimal replenishment strategies. We then show that the owner of the firm can manage the divisions as cost centers without compromising the systemwide performance. This is achieved by using an incentive-compatible measurement scheme based on accounting inventory levels. Finally, we investigate the impact of irrational behavior on supply chain performance and demonstrate that it is important for the upstream members of the supply chain to have access to accurate customer demand information.